Metode v nuklearni medicini v diagnostiki raka dojk - Movrin, Tadeja (Radiology and oncology (Ljubljana), 1998)
Mammography and ultrasound are dominant modalities in evaluating patient suspected of breast cancer around the world and our country. But both of them has been shown to be inaccurate in patiens with the dense breast or in the breast where significant architectural distortion has occurred. Recent reportsindicate methoxyisobutylisonitrile (MIBI) that rely on biochemical and physiological characteristics of tumor, to be promising in the evaluation of the patients whose mammograms are difficult to be evaluated.
Keywords: Breast neoplasms; diagnostika; dojke; metode; novotvorbe; nuklearna medicina; Radionuclide imaging; rak (medicina); Technetium